(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This study refers the attitude of the students in involving themselves in adult education programme. By reviewing review of literature researcher found that, the scope of the study is very limited because of limited time, and the resources at the disposal of the researcher to study the attitude of all the students. Hence this investigation is confined to study the junior colleges, degree college and post-graduate students only. In this study the investigator has taken the students of different age groups and of both sexes with two localities namely urban and rural as variables. A few more important variables considered for the present study are the father’s employment, mother’s employment.